SISTEM INFORMASI PEMBAYARAN IURAN KEAMANAN DAN KEBERSIHAN PADA PERUMAHAN BERBASIS WEBSITE MENGGUNAKAN METODE DESIGN THINKING: Array - Siregar, Wandani; Irvan, Irvan; Rahayu, Eka (Universitas Harapan Medan, 2020)
Housing is a basic human need and needs to be fostered and developed for the survival and enhancement of people's lives and livelihoods and settlements cannot be seen as mere suggestions of needs, but more than that it is a process of settling in creating a living space to socialize themselves and reveal their identity. The development method in building a Security and Cleanliness Contribution Payment Information System in Menteng Indah Housing Based on Website based on the theory of design thinking methods. Design thinking is a method used to solve problems encountered by gathering lots of ideas in brainstorming sessions using a user-centered approach. The research test is to produce a Fee Payment System in Website-Based Menteng Indah Housing, with the application of this system will facilitate citizens and security in the process of paying fees